Analisa Faktor Penyebab Kegagalan Sister Cities di Indonesia - Nablia Safitri; Sisilia Putri Syafira; Dyah Estu Kurniawati (Jayapangus Press, 2023)
This study aims to analyze the failure of cooperation sister city. This research focuses on cooperation sister cities carried out by several local governments, which leads to the unsuccessful achievement of cooperation or even failure. The complexity of issues in international relations facilitates the emergence of local actors who play a role in foreign relations activities. The emergence of this sub-state actor is one of the impacts of a country's decentralization and regional autonomy policies so that the regions can participate in foreign relations. This study uses qualitative research methods through a literature review. In analyzing qualitative data, the author uses software, computer namely vosviewer. This study uses 20 journals from various cities in Indonesia that discuss the failure of sister cities. This study concludes that not all collaborations can run smoothly or as agreed. The failure occurred due to two factors, namely internal and external factors. The internal factors that occurred were the lack of communication between the two cities and the absence of significant results related to cooperation, then several external factors that occurred, such as changes in policies of the two regions, then policies at the global level impact on the state and influence local government policies.